1983
DOI: 10.1136/bmj.286.6358.12
|View full text |Cite
|
Sign up to set email alerts
|

Laser treatment for carcinoma of the bronchus.

Abstract: References lAlexopoulos KA. The importance of breech delivery in the pathogenesis of brain damage. Clin Pediatr (Phila) 1973;12:248-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 8 publications
0
16
1
Order By: Relevance
“…In addition, care must be taken to avoid spillage of pus after relief of obstruction. Hetzel and associates [63] reported that reexpansion of completely collapsed lung led to fatal pneumonia in 2 of 3 patients.…”
Section: Airway Obstructionmentioning
confidence: 98%
“…In addition, care must be taken to avoid spillage of pus after relief of obstruction. Hetzel and associates [63] reported that reexpansion of completely collapsed lung led to fatal pneumonia in 2 of 3 patients.…”
Section: Airway Obstructionmentioning
confidence: 98%
“…Recently local, palliative laser treatment of endobronchial carcinoma via the fibrescope has been assessed (Hetzel et al, 1983). In 34 patients, good palliation was achieved in just over 50o.…”
Section: Therapeutic Bronchoscopymentioning
confidence: 99%
“…However, in the latter situation fulminating infections have occurred perhaps due to aspiration of the trapped contents distal to the blockage (Hetzel et al, 1983).…”
Section: Cytotoxic Chemotherapymentioning
confidence: 99%